SIRT1/PGC-1α Signaling Promotes Mitochondrial Functional Recovery and Reduces Apoptosis after Intracerebral Hemorrhage in Rats - Zhou, Yang; Wang, Shaohua; Li, Yixin; Yu, Shanshan; Zhao, Yong (Frontiers in Molecular Neuroscience, 2018)
Silent information regulator 1 (SIRT1) exerts neuroprotection in many neurodegenerative diseases. However, it is not clear if SIRT1 has protective effects after intracerebral hemorrhage (ICH)-induced brain injury in rats. Thus, our goal was to examine the influence of SIRT1 on ICH injuries and any underlying mechanisms of this influence. Brain injury was induced by autologous arterial blood (60 μL) injection into rat brains, and data show that activation of SIRT1 with SRT1720 (5 mg/kg) restored nuclear SIRT1, deacetylation of PGC-1α, and mitochondrial biogenesis and decreased mortality, behavioral deficits, and brain water content without significant changes in phosphorylated AMP-activated protein kinase (pAMPK) induced by ICH. Activation of SIRT1 with SRT1720 also restored mitochondrial electron transport chain proteins and decreased apoptotic proteins in ICH; however, these changes were reversed after ICH. In contrast, treatment with PGC-1α siRNA yielded opposite effects. To explore the protective effects of SIRT1 after ICH, siRNAs were used to knockdown SIRT1. Treatment with SIRT1 siRNA increased mortality, behavioral deficits, brain water content, mitochondrial dysfunction, and neurocyte apoptosis after ICH. Thus, activation of SIRT1 promotes recovery of mitochondrial protein and function by increasing mitochondrial biogenesis and reduces apoptosis after ICH via the PGC-1α mitochondrial pathway. These data may suggest a new therapeutic approach for ICH injuries.